Ethical Deception? Responding to Parallel Subjectivities in People Living with Dementia - Matilda Carter (Disability Studies Quarterly, 2020)
Many caregivers feel that they need to lie or withhold the truth from people living with dementia, but worry that, in doing so, they are violating a duty to tell the truth. In this article, I argue that withholding the truth from and, in limited circumstances, lying to people living with dementia is not only morally permissible, but morally required by a more general requirement that we treat each other as persons worthy of respect. I do so through an analysis of the groundings of the duty to tell the truth, and a critical reflection on its cognitively ableist construction.
Keywords: Dementia; social equality; respect